Визначення доцільних обсягів використання енергозберігаючих технологій в житлово-комунальному господарстві - Denysov V.A. (General Energy Institute of the National Academy of Sciences of Ukraine, 2012)
A hierarchical model and software-informational means are offered for the determination of the expedient size of the use of energy-saving technologies in the sector of housing and communal facilities considered as a complex dynamical controllable system with beforehand set hierarchical structure. The task of hierarchical control over such a system is formulated. The formation of the optimum aggregate of directions and volumes of financing the energy-saving measures in the sector of housing and communal facilities is considered.